Housing in the Northwest Territories: the Post-War Vision - Robson, Robert (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1995)
The delivery of housing programs in the Northwest Territories in the post—World War II era was part and parcel of government's newly defined northern mandate. Often described as the "northern vision", the northern mandate was a wide ranging initiative that provided for government-orchestrated, northern expansion. Precipitated by both the federal and the territorial governments, the housing programs as delivered under the auspices of the northern vision, more readily provided for the expansionary needs of government than for the shelter needs of the northern residents.